Impact of early diagnosis on surgical outcomes in patients with Loeys-Dietz syndrome - Kim, Hongsun; Lee, Jun Ho; Chung, Su Ryeun; Park, Pyo Won; Park, Taek Kyu; Kang, I-Seok; Huh, June; Kim, Duk-Kyung; Cho, Yang Hyun; Sung, Kiick (Frontiers in Cardiovascular Medicine, 2024)
Background This study aimed to investigate the influence of early diagnosis (ED) on surgical outcomes in patients definitively diagnosed with Loeys-Dietz syndrome (LDS). Methods A retrospective review was conducted on 38 patients with LDS who underwent aortic surgery at our institution between January 1995 and June 2022. The primary endpoint was freedom from aortic reoperation. Results Among the patients, the median age at the initial surgery was 33 (range: 39–44) years, and 23 (60.5%) patients were male. Twenty-one (55.3%; aortic dissection or rupture (n = 2) and aneurysm (n = 19)) patients were diagnosed with LDS before the initial surgery (ED group). Meanwhile, the remaining 17 (44.7%; aortic dissection or rupture (n = 13) and aneurysm (n = 4)) patients were after surgery [delayed diagnosis (DD) group]. The ED group had significantly lower rates of emergency surgery and concomitant arch procedure (P < .001, respectively) but a higher rate of valve-sparing root surgery (P = .018) compared to the DD group. No in-hospital mortality was observed in either group. Nevertheless, the ED group had a shorter postoperative hospital stay (median difference: 3 days, P = .032) and a lower rate of aortic reoperation (P = .013). Conclusion Early detection of LDS may help in preventing acute aortic syndrome, reducing the risk of aortic reoperation, and potentially shortening hospital stay. Careful medical management before surgery could contribute to better clinical outcomes and an improved quality of life for patients with LDS.